2001
DOI: 10.1073/pnas.111606798
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, local adaptation of zooplankton behavior to changes in predation pressure in the absence of neutral genetic changes

Abstract: Organisms producing resting stages provide unique opportunities for reconstructing the genetic history of natural populations. Diapausing seeds and eggs often are preserved in large numbers, representing entire populations captured in an evolutionary inert state for decades and even centuries. Starting from a natural resting egg bank of the waterflea Daphnia, we compare the evolutionary rates of change in an adaptive quantitative trait with those in selectively neutral DNA markers, thus effectively testing whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
466
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(474 citation statements)
references
References 22 publications
5
466
2
1
Order By: Relevance
“…One caveat applies to our conclusion of no genetic substructuring within the European eel, namely that the absence of, or a very weak, geographical differentiation at neutral loci does not preclude the existence of more pronounced differences at loci affected by selection (Cousyn et al 2001;Koskinen et al 2002). Since selected and non-selected genes can have different effective migration rates, adaptive differences could in theory persist in spite of significant neutral gene flow.…”
Section: Discussionmentioning
confidence: 75%
“…One caveat applies to our conclusion of no genetic substructuring within the European eel, namely that the absence of, or a very weak, geographical differentiation at neutral loci does not preclude the existence of more pronounced differences at loci affected by selection (Cousyn et al 2001;Koskinen et al 2002). Since selected and non-selected genes can have different effective migration rates, adaptive differences could in theory persist in spite of significant neutral gene flow.…”
Section: Discussionmentioning
confidence: 75%
“…Khibnik & Kondrashov 1997). In many cases, however, evolutionary change can occur at rates comparable to the rates at which the abundances of populations and communities change and a growing number of studies have demonstrated rapid evolution at ecologically relevant time-scales (Thompson 1998;Hairston et al 1999;Hendry et al 2000;Cousyn et al 2001;Reznick & Ghalambor 2001;Stockwell et al 2003). In this study, we show how clonal selection operating on a fundamental life-history trait (the production of amictic versus mictic offspring) affects the dynamics of plankton populations.…”
Section: Introductionmentioning
confidence: 91%
“…Species as diverse as single-celled algae, annual plants, birds, fishes, crustaceans, insects and sheep are found to undergo rapid contemporary evolutionary changes in traits that adapt them within a few generations to changing or new environments (Reznick et al 1997;Thompson 1998;Hairston et al 1999;Sinervo et al 2000;Cousyn et al 2001;Reznick & Ghalambor 2001;Grant & Grant 2002;Heath et al 2003;Yoshida et al 2003;Olsen et al 2004;Pelletier et al 2007;Swain et al 2007). Thus, the old assumption that evolutionary change is negligible on the time-scale of ecological interactions is now demonstrably incorrect.…”
Section: Introductionmentioning
confidence: 99%